A ossatura poética de José Paulo Paes - Duarte, Madileide de Oliveira (2001)
This paper will show the essence of José Paulo Paes‟ poetic language. In order to derive our conclusions, we analyzed José Paulo Paes‟ poetry, his translations and his literary criticisms. For a general thechnical reference, we used Charles Sanders Peirce‟s Semiotic. For the more detailed aspects of our analysis, we reference the readings of Roman Jakobson, Haroldo de Campos, Lúcia Santaella, Décio Pignatari, Sussana Busato, Ezra Pound, Leyla Perrone Moysés, Walter Benjamin, Jeanne Marie Gabnebin, Maria José Palo and Maria D‟Oliveira. Thus we will show how José Paulo Paes‟ poetry in the area of modernism, concretism and children‟s poetry reveal common aspects of style, primarily concisiveness, sentiment ability, wordplay and the use of novel words not yet officially part of the language.